Risk Factors for COVID-19: A Quantitative Study Conducted at Padang City Center Hospital - Martini, Rose Dinda; Dorisnita; Hartati (International Journal of Statistics in Medical Research, 2023)
Objective: This study sought to estimate the prevalence of COVID-19 infection among hospital staff according to various factors. Moreover, it sought to identify any factors that predicted a higher probability of infection in this population. Methods: This descriptive research was conducted among medical and non-medical personnel at Padang City Center Hospital, Indonesia (n=129). A chi-square test analysis was used to determine the degree of interrelationship between the studied variables, while an odds ratio (OR) test was performed to identify more potential categories. Results: Some 31.8% of respondents tested positive for COVID-19, although this finding was insignificant (p>0.05). In terms of the OR, the following probabilities were calculated: age (OR=1.0 [0.36–2.88]); medical history (OR=1.3 [0.23–2.0]); higher education (OR=1.9 [0.2–17.6]); wearing a good mask (OR=0.7 [0.07–7.02]); good hand washing (OR=1.8 [0.46–7.07]); good physical distancing (OR=1.8 [0.46–7.07]); good personal protective equipment (OR=0.7 [0.07–7.02]); normal depression, anxiety, and stress (OR<1.0); and comorbidity (OR=1,2 [0.46-3.06]). Conclusion: No significant relationship was found between the studied factors and COVID-19 infection. However, there were more potential trends, especially for highly educated medical teams, not wearing a mask, smoking, engaging in strenuous activity, poor psychology, and comorbidity. These findings should prompt policymakers tasked with developing resources and interventions to pay more attention to the needs of medical and non-medical staff during the COVID-19 pandemic, especially the availability of masks.